Development and Validation of an Integrated Technological Pedagogical Content Knowledge and Education for Sustainable Development Assessment Rubric for Pre-Service Science Teachers - Safriana Safriana; Ade Irfan; Lidya Rosnita; Ayu Rahmi; Amir Karimi (Universitas Syiah Kuala, 2026)
This study addressed the absence of assessment instruments that simultaneously capture the integration of technology, pedagogy, and content with sustainability-oriented competencies in science teacher education. It aimed to develop and validate an assessment rubric that integrates technological pedagogical content knowledge (TPACK) with education for sustainable development (ESD) for pre-service science teachers. The rubric was developed through an iterative research and development process involving literature-based construct mapping, expert review, and quantitative content validation. Three expert validators evaluated 20 rubric items, and Aiken’s V was used to quantify content validity. The results showed item-level Aiken’s V values ranging from 0.78 to 1.00, with 18 items in the very high category and 2 items in the high category, and an overall V of 0.96, indicating excellent expert agreement. These findings demonstrate that the rubric provides a valid and conceptually robust tool for assessing pre-service science teachers’ ability to design technology-enhanced, sustainability-oriented science lessons. The rubric can support formative and summative assessment in teacher education programs and offers a foundation for future empirical and comparative studies on TPACK–ESD competence